Der Internist, Konstitutionspathologe und Sportmediziner Hermann Rautmann (1885–1956) - Metzger, Nadine (Sudhoffs Archiv; Zeitschrift für Wissenschaftsgeschichte, 2020)
In the 1920s, Freiburg internist Hermann Rautmann (1885–1956) contributed heavily to the then flourishing fields of constitutional medicine and sports medicine, being a notable figure in early medical statistics and heading the first university institute for sports medicine. However, in 1929 Rautmann left academic medicine in favour of a permanent position at Brunswick municipal hospital where he spent the rest of his professional life. Even so Rautmann’s promising university career was thus cut short he quickly regained his feet and established new ties to intellectually stimulating and professionally satisfying domains, e. g. aviation medicine, the Technical College Brunswick, and the Brunswick Academic Society. This article presents the first biography of this versatile medical scientist, including his ambivalent nazi years and rebuilding post-war activities – beyond university.
CRIS-Team Scopus Importer:2024-12-16
Keywords: academic career; Brunswick; constitutional medicine; medical statistics; physicians under nazism; sports medicine